Pattern Based Frequent Term Retrieval Search Using Text Clustering - Krithika, R; Sathish Kumar, G (International Journal of Computer Sciences and Engineering, 2025)
Clients are known to experience troubles in dealing with information retrieval look outputs, particularly if those yields are above a certain size. It has been contended by several analysts that look yield Clustering can help clients in their collaboration with IR frameworks in some retrieval situations, providing them with an review of their results by abusing the topicality information that resides in the yield but has not been used at the retrieval stage. This review might enable them to find applicable records more effortlessly by focused on the most promising clusters, or to use the Groups as a starting-point for question refinement or expansion. In this paper, the results of tests carried out to assess the viability of Clustering as a look yield presentation technique are reported and discussed.